Vertical Distribution Of Hard Corals In Southern Siladen Island - John L. Tombokan; Unstain N. W. J. Rembet; Silvester B. Pratasik (Jurnal Ilmiah PLATAX, 2017)
This study was aimed at provide information on hard coral distribution in southern Siladen Island. The work was done using SCUBA gear Line Intercept Transect (LIT). Thirty m long-line transects were placed at the reef flat, 5 m depth, 10 m depth, 15 m depth, and 20 m depth. A total of 44 hard coral genera was recorded, and the highest number of genre was found at 5 m depth. Coral species diversity was also high enough at the reef flat (1.032) and 5 m depth (1.28). Coral reef condition at 10 m depth was good enough as well and categorized as productive due to much higher percent of the biotic component than the abiotic component. The dominant life forms consisted of tabulate Acropora and branching corals at the reef flat, encrusting corals, branching corals, and foliose corals at 5 m, encrusting corals at 10 and 20 m depth, and massive corals, encrusting corals, and branching corals at 15 m depth, respectively. Keywords: coral reef, distribution, LIT, vertical zonationl. Â  Abstrak Penelitian ini bertujuan untuk menyediakan informasi tentang distribusi karang batu di sebelah selatan pulau Siladen. Penelitian ini dilakukan menggunakan alat selam SCUBA dan metode transek intersep garis. Tali transek sepanjang 30 m diletakkan di rataan terumbu, kedalaman 5, 10, 15, dan 20 m. Total 44 genera karang batu ditemukan pada penelitian ini, dan jumlah genera terbanyak ditemukan pada kedalaman 5 m. Keanekaragaman spesies karang juga cukup tinggi di daerah rataan terumbu (1,032) and 5m (1,28). Kondisi terumbu karang pada kedalaman 10 m juga cukup baik dan dikategorikan produktif karena tingginya komponen biotik dibandingkan dengan komponen abiotik. Bentuk pertumbuhan yang dominan masing-masing terdiri dari Acropora meja dan karang bercabang di rataan terumbu karang, karang encrusting, karang bercabang, dan foliose pada kedalaman 5 m, karang encrusting pada kedalaman 10 dan 20m, serta karang masif, karang encrusting dan karang bercabang pada kedalaman 15m. Â  Kata kunci: Terumbu karang, distribusi, Transek Intersep Garis, Zonasi vertikal.